KAPITALISME DAN PENDIDIKAN LIBERAL KAPITALISTIK - Rappe Rappe (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2011)
This paper entitled capitalism and capitalistic liberal education will present two problems related to the aforementioned theme, they are: how capitalism exists in social life and what is capitalistic liberal education. To deal the first problem, the writer traces the origin of capitalism internationally up to the latest con-dition. The study found that capitalism developed as an antithesis toward secularism and materialism. At the first stage of its deve-lopment, capitalism signified a religious Puritanism then turned to secularism movement. This finally turned to two different movements, rational and irrational capitalism. The second issue of this paper deals the capitalistic liberal education system. Based on the brief description of this, it can be inferred that capitalistic liberal education is all forms of educational management designed for merely getting financial interest without considering students’ interest on education.